Sets, logic, computation : an open text - Zach, Richard; Burns, Samara; Hagg, Dana; BC Open Textbook Project; BCcampus (Richard Zach, 2017)
"This textbook is based on the Open Logic Project. It covers naive set theory, first-order logic, sequent calculus and natural deduction, the completeness, compactness, and Löwenheim-Skolem theorems, Turing machines, and the undecidability of the halting problem and of first-order logic"--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on April 11, 2019).
Keywords: Logic -- Textbooks; Electronic books